Naturally absorbed lithium may prevent suicide attempts and deliberate self-harm while eicosapentaenoic acid may prevent deliberate self-harm and arachidonic acid may be a risk factor for deliberate self-harm: The updated different findings in new analyses - Izumi, Toshihiko; Kanehisa, Masayuki; Terao, Takeshi; Shiotsuki, Ippei; Shirahama, Masanao; Satoh, Moriaki; Muronaga, Masaaki; Kohno, Kentaro; Hirakawa, Hirofumi; Etoh, Masaki; Matsukawa, Takehisa (Frontiers in Psychiatry, 2022)
Background Since our previous investigation on the effects of trace lithium, eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and arachidonic acid (AA) on deliberate self-harm and suicide attempts in 2018, to our knowledge, no replication study has been conducted on this topic. Subjects and methods We increased 37 new patients and totally 234 patients were re-analyzed to further investigate the association of suicide-related behaviors with levels of trace lithium, EPA, DHA, and AA in a different way to avoid multicollinearity. Results Higher lithium levels were significantly associated with fewer suicide attempts and deliberate self-harm, higher EPA levels were significantly associated with fewer deliberate self-harm, and higher AA levels were significantly associated with more deliberate self-harm. Discussion Although the sample size was only slightly larger than the previous study, the present results were clearly different from the previous ones due to the use of different statistical analyses to avoid multicollinearity. Conclusion The present findings suggest that naturally absorbed lithium may protect against suicide and deliberate self-harm, while naturally absorbed EPA may protect against deliberate self-harm. However, naturally absorbed AA may be a risk factor for deliberate self-harm.